Associations of depression and anxiety symptoms with sexual behaviour in women and heterosexual men attending sexual health clinics: a cross-sectional study. (27th February 2019) - Coyle, Rachel Margaret; Lampe, Fiona C; Miltz, Ada Rose; Sewell, Janey; Anderson, Jane; Apea, Vanessa; Collins, Simon; Dhairyawan, Rageshri; Johnson, Anne M; Lascar, Monica; Mann, Sue; O'Connell, Rebecca; et al.
Abstract : Objective: To assess the association of symptoms of depression and anxiety with sexual risk behaviour and history, among women and heterosexual men attending genitourinary medicine (GUM) clinics. Methods: Attitudes to and Understanding of Risk of Acquisition of HIV (AURAH) was a cross-sectional, self-administered questionnaire study recruited from 20 GUM clinics in England, 2013–2014. This analysis included women and heterosexual men. The prevalence of depression and anxiety symptoms was assessed. Modified Poisson regression was used to produce adjusted prevalence ratios (aPR) for the association of t demographic, socioeconomic and lifestyle factors with depression and anxiety, adjusted for gender, age, ethnicity, education level and study region. Among individuals reporting sex in the past 3 months, associations of depression and anxiety with sexual risk behaviour and history were assessed separately by gender, adjusted for age, ethnicity, study region, education and relationship status. Results: Questionnaires were completed by 676 women and 470 heterosexual men. Depression symptoms were reported by 100 (14.8%) women and 33 men (7.0%). Anxiety symptoms were reported by 79 women (11.7%) and 21 men (4.5%). Among women reporting recent sex, those with depression symptoms were more likely to report condomless sex with a non-regular partner, aPR 1.38 (1.07–1.77) and recent condomless sex with two or more partners, 1.80 (1.25–2.59). Women with anxiety symptoms more likely to report recent condomless sex with two or more partners, 1.68 (1.13–2.50), low self-efficacy for condom use, 1.54 (1.02–2.31) and STI diagnosis in the last year 1.51 (1.04–2.20). Among heterosexual men reporting recent sex, depression and anxiety symptoms were associated with low self-efficacy with condom use, 2.32 (1.29–4.19) for depression and 2.23 (1.26–3.94) for anxiety, but not with measures of condomless sex. Discussion: The associations between psychological symptoms and sexual risk behaviours highlight the importance of holistic assessment of need by both general and sexual health clinicians. We highlight the challenge in delivering holistic care associated with fragmentation of sexual health services.